Implementación de un sistema de gestión documental administrativa aplicando la tecnología php bajo el framework codeigniter, html5, css3 y mysql para la unidad académica de ciencias de la ingeniería y aplicadas de la universidad técnica de cotopaxi en el periodo 2015 – 2016 - Centeno Defas, Elvis Paúl (2016)
The current researching work has as a main objective, to implement an Administrative Documental Management System at Academic Unit of Engineering and Aapplied Sciences at Cotopaxi Technical University where the purpose is to control different procedures which are daily done in the developing of academic activities, optimizing students and administrative stuff, one of the functions is the carrying out procedures through mobile devices on the Internet. Using free tools and XP methodology which allow us to give a solution that makes easy the process at Academic Unit. For theoretical basis, applicants use bibliographic, virtual and on-site researching to get information to analyze; survey is the applied technique using a questionnaire….